A Different Manifest Destiny : U.S. Southern Identity and Citizenship in Nineteenth-Century South America - Wolnisty, Claire M. (Book collections on Project MUSE., 2020)
"A Different Manifest Destiny traces the way in which southerners capitalized on Latin American connections to promote visions of modernity compatible with slave labor from the antebellum to the Civil War era"--